Analysis of the First Round of 2018 Government Election for the State of Rio de Janeiro Based on Twitter - Rubin, Francis Spiegel; de Almeida, Yuri Luz; Alvim, Adriana Cesario de Faria; Dias, Vânia Félix; dos Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
Social networks such as Twitter have become the main platforms for political debate in the field of Information Systems, making it an effective tool for candidates and parties to promote campaigns and government projects. In this context, this study aims to understand the dynamics of campaigns in Twitter during the first round of the government election in the State of Rio de Janeiro, Brazil, in 2018, and whether the electoral dispute was reflected in any way by activities on such platform. The approach involved observing candidates and users behaviors based on posts and interactions. We noticed the presence of automated accounts during the campaign, using the Botometer API and cross-validating the collected data set for the selected election period. Finally, the most active and most cited candidate was not the first one in the dispute, and the sudden change that occurred in the last days of the electoral race was noticed.